2000
DOI: 10.1002/(sici)1097-0142(20000215)88:4<755::aid-cncr4>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous polyposis coli I1307K mutation in Jewish patients with different ethnicity

Abstract: BACKGROUND A new mutation, I1307K, recently was reported in the adenomatous polyposis coli (APC) gene. This mutation was found to be predominant in Ashkenazi Jews, creating a hypermutable area and predisposing the development of carcinoma. The objective of the current study was to estimate the prevalence of this mutation in several of the ethnic groups that comprise the Israeli population and to elucidate the clinical features of the mutation carriers with colorectal carcinoma (CRC). METHODS A total of 111 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
23
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
7
23
0
2
Order By: Relevance
“…This finding is counter-intuitive, as the prevailing paradigm of cancer susceptibility genes predicts that mutation carriers will exhibit early age at onset, and have a personal or a family history of cancer more frequently than sporadic cases. The findings of a similar age at onset and family history of cancer in mutation carriers and non-carriers reported herein are consistent with another study (Drucker et al, 2000). Taken together with the reports that adenomatous colonic polyps were not more prevalent in I1307K mutation carriers compared with non-carriers (Syngal et al, 2000;Stern et al, 2001), these findings imply that the I1307K APC mutation confers a moderate increased lifetime risk for CRC (Woodage et al, 1998;Gryfe et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is counter-intuitive, as the prevailing paradigm of cancer susceptibility genes predicts that mutation carriers will exhibit early age at onset, and have a personal or a family history of cancer more frequently than sporadic cases. The findings of a similar age at onset and family history of cancer in mutation carriers and non-carriers reported herein are consistent with another study (Drucker et al, 2000). Taken together with the reports that adenomatous colonic polyps were not more prevalent in I1307K mutation carriers compared with non-carriers (Syngal et al, 2000;Stern et al, 2001), these findings imply that the I1307K APC mutation confers a moderate increased lifetime risk for CRC (Woodage et al, 1998;Gryfe et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, we previously showed that the mutation probably represents a founder mutation in Jewish individuals (Patael et al, 1998), as was also confirmed by other investigators (Woodage et al, 1998). Drucker et al (2000), reported that the I1307K mutation was detected in 3/4 Yemenite Jewish individuals, whereas in the present study this mutation could not be detected in any of 18 Yemenite Jews with CRC. This discrepancy cannot be logically settled, until more individuals of Yemenite extraction are tested.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…7 This variant has been reported exclusively in the Ashkenazi 2,7,8 and Yemenite Jewish populations. 9 Like the I1307K variant, the E1317Q variant results in a charge difference from a single amino acid change. 6 As opposed to the I1307K variant, this variant is present in both Ashkenazi Jewish and non-Ashkenazi Jewish Caucasian populations, and is believed to predispose to colonic adenomas and carcinomas.…”
mentioning
confidence: 99%